Teachers' Understanding of The Integration of Islamic Values in Mathematics Learning in Elementary Schools - Hadi, Susilo; Hartono, Hartono; Rachmadtullah, Reza (Eduprof : Islamic Education Journal, 2025)
This study aims to explore the understanding and application of the integration of Islamic values ​​in mathematics learning in elementary schools. Using a descriptive qualitative approach with a phenomenological design, this study involved interviews, observations, and documentation to obtain the views of mathematics teachers who teach in elementary schools with a religion-based curriculum. The results showed that teachers' understanding of the integration of Islamic values ​​varied, with some teachers emphasizing more on ethical and moral aspects, while others focused on spirituality and the order of the universe reflected in mathematics. The integration of values ​​such as honesty, patience, and responsibility is considered to be able to enrich students' understanding of mathematics material while shaping their moral character. However, the challenge faced is how to effectively connect mathematical concepts with religious values ​​in the existing curriculum. Active and project-based learning methods have proven effective in integrating Islamic values, although teachers still face difficulties in implementing them. This study is expected to contribute to the development of learning models that integrate religious values ​​in mathematics education in elementary schools.